2021
DOI: 10.1111/eci.13515
|View full text |Cite
|
Sign up to set email alerts
|

Building‐up fit muscles for the future

Abstract: Special issue -In Utero and Early Life Programming of Aging and Disease'.Skeletal muscle (SM) adaptations to physical exercise (PE) have been extensively studied due, not only to the relevance of its in situ plasticity, but also to the SM endocrine-like effects in noncontractile tissues, such as brain, liver or adipocytes.Regular PE has been considered a pleiotropic nonpharmacological strategy to prevent and counteract the deleterious consequences of several metabolic, cardiovascular, oncological and neurodege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 100 publications
(284 reference statements)
0
5
0
Order By: Relevance
“…Indeed, maternal lowprotein diet [251,252] or high-fat diet (HFD) [253,254] consumption affect muscle metabolism and insulin sensitivity, predisposing the offspring to metabolic dysfunction later in life [255][256][257][258], in part by epigenetically altering skeletal muscle gene expression [259][260][261]. Moreover, maternal HFD correlates with compromised skeletal muscle development in the offspring, characterized by atrophy [253,262,263] and reduced performance [264,265], in part due to mitochondrial defects [263,266,267]. Even paternal nutrient support influences the metabolic state and the predisposition to metabolic disease [268,269], by epigenetic reprogramming of the sperm and offspring metabolic genes [270].…”
Section: Inter-or Transgenerational Effects Of Nutrients and Exercise On Skeletal Muscle Massmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, maternal lowprotein diet [251,252] or high-fat diet (HFD) [253,254] consumption affect muscle metabolism and insulin sensitivity, predisposing the offspring to metabolic dysfunction later in life [255][256][257][258], in part by epigenetically altering skeletal muscle gene expression [259][260][261]. Moreover, maternal HFD correlates with compromised skeletal muscle development in the offspring, characterized by atrophy [253,262,263] and reduced performance [264,265], in part due to mitochondrial defects [263,266,267]. Even paternal nutrient support influences the metabolic state and the predisposition to metabolic disease [268,269], by epigenetic reprogramming of the sperm and offspring metabolic genes [270].…”
Section: Inter-or Transgenerational Effects Of Nutrients and Exercise On Skeletal Muscle Massmentioning
confidence: 99%
“…Recently, the beneficial effects of exercise have been shown to be transmitted to future generations, since parental physical exercise positively affects body metabolism, skeletal muscle structure, and performance of the offspring [263,273,284]. Studies from human and animal models demonstrated that maternal exercise performed during pregnancy increases muscle motility, reduces predisposition to obesity, and improves glucose homeostasis in the offspring [273,[285][286][287][288].…”
Section: Inter-or Transgenerational Effects Of Nutrients and Exercise On Skeletal Muscle Massmentioning
confidence: 99%
“…It has been proven that skeletal muscle is a programmable tissue and can "remember" mechanical and metabolic stimuli in the early stages of life through epigenetic mechanisms, which affects its function throughout lifetime [46,47]. Epigenetic memory effects have recently been illustrated for key genes involved in mitochondrial biogenesis, including the most comprehensive transcription coactivator controlling energy metabolismi.e.…”
Section: Mother's Physical Activitymentioning
confidence: 99%
“…Beleza et al 9 address the topic 'Buildingup fit muscles for the future'. The authors emphasize that regular physical exercise is beneficial to improvement of health in multiple chronic conditions.…”
Section: General Review Of Contents By Peter Nathanielszmentioning
confidence: 99%